The Effect of the Promotion of Clean and Healthy Lifestyle in Ujong Tanjung Elementary School Through the SAL (Snake and Ladder) Media - Susy Sriwahyuni; Zakiyuddin Zakiyuddin; Muhammad Reza Firdaus (Universitas Teuku Umar, 2021)
School age children are groups that is prone to experiencing health problems due to low knowledge of clean and healthy life behavior. To increase their knowledge, an attractive promotional media namely snake and ladder is needed so that the delivery of material is easily accepted by them. The purpose of this method is as a stimulus medium so that elementary school students can easily understand on how to improve clean and healthy life behavior. The research method was quasi-experimental with One-Group Pretest-Posttest Design. The population were 85 elementary school students of Ujong Tanjung in IV, V and VI grade who had been given an understanding of CHLB. The sample consisted of 30 people who would be given a pre-test and post-test who were previously given snake and ladder media intervention. The results showed there was a significant improvement on student’s knowledge after they got intervention with snake and ladder media where during the pre-test the respondents who had good knowledge were 11 people (36.7%) but after being given the intervention, it was increase into 22 people (73.3%). On the other hand, respondents with poor knowledge category on pre-test were 19 people (63.3%), after being given the intervention, it was decrease into 8 people (26.7%). Based on the results of Wilcoxon test, it was found Pvalue = 0,000 < α =0.05, it is indicated there is a significant difference on respondents’ knowledge about clean and healthy life behavior (CHLB) before and after given the intervention through Snake and Ladder (SAL) media. The conclusion is there is the difference in the level of respondents’ knowledge on CHLB (Clean and Healthy Living Behavior) before and after the intervention through Snake and Ladder (SAL) media.